An Objective Study of Anatomic Shifts in Intracranial Hypotension Using Four Anatomic Planes - Shamar J. Young; Ronald G. Quisling; Sharatchandra Bidari; Tina S. Sanghvi (Radiology Research and Practice)
Purpose. Intracranial hypotension (IH) often remains undetected using current MR diagnostic criteria. This project aims to demonstrate that central incisural herniation is highly effective in helping to make this diagnosis. Materials and Methods. Magnetic resonance imaging (MRI) was analyzed in 200 normal and 81 clinically known IH patients. MRI reference lines approximating the plane of the incisura, the plane of the diaphragma sella, the plane of the foramen magnum, and the plane of the visual pathway were utilized to measure the position of selected brain structures relative to these reference lines. Results. All IH patients had highly statistically significant (p<0.0001) measurable evidence of downward central incisural herniation when compared to normal controls. The first of the important observations was a downward shift of the mammillary bodies, which shortened the midsagittal width of the interpeduncular fossa cistern. A concurrent downward shift and deformity of the tuber cinereum accompanied the mammillary body shift. The second essential observation was an abnormal clockwise rotation of the long axis of the visual pathway. A severity grading system is proposed based on the extent of these shifts as well as secondary shifts of the brain stem, splenium, and cerebellar tonsils. Conclusion. This study objectively delineates the anatomic shifts of brain structures adjacent to the incisura and foramen magnum. This methodology is sufficient to recognize the features of IH and to stratify the spectrum of IH findings into a functional grading system for quantifying the results of interventional therapy.